Influence of muscle depth and thickness on ultrasound echo intensity of the vastus lateralis. (September 2021) - Varanoske, Alyssa N; Coker, Nicholas A; Johnson, Bri-Ana DI; Belity, Tal; Wells, Adam J
Background: Ultrasonography is used to evaluate muscle quality (i.e. echo intensity [EI]), but an attenuation of ultrasound waves occurs in deeper tissues, potentially affecting these measures. Purpose: To determine whether muscle thickness (MT) affects EI and if EI varies between the superficial and deep portions of the muscle. Materials and Methods: MT, EI, subcutaneous adipose tissue thickness (SAT), tissue depth (DISDEEP ), and EI of the overall (EIFULL ) as well as deep (EIDEEP ) and superficial (EISUPF ) portions of the vastus lateralis (VL) were assessed in 33 resistance-trained males using ultrasonography. The difference (EIDIFF ) between EISUPF and EIDEEP was calculated. Mean differences between EIFULL, EISUPF, and EIDEEP were analyzed using a repeated-measures analysis of variance (ANOVA). Relationships between measures of muscle depth/ thickness and EI were examined using Pearson's r . Results: EISUPF was greater than EIDEEP ( P  < 0.001) and EIFULL ( P  < 0.001). MT was negatively correlated with EIFULL ( P  < 0.001) and positively correlated with EIDIFF ( P  < 0.001). SAT was not correlated with any EI measure, but DISDEEP was positively correlated with EIDIFF ( P  < 0.001). Conclusion: EI of the VL is heterogeneous, as the deeper portion produces lower values than the superficial portion. Thicker muscles present lower EI but have greater discrepancies in EI between the superficial and deep portions. Although SAT was not correlated with EI, DISDEEP was related to EIDIFF, demonstrating that the combination of MT and SAT should be considered when evaluating muscle quality. Future research is necessary to determine if changes in EI following resistance training are driven by increases in MT.